2022
DOI: 10.3171/2021.7.spine21829
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and complications of minimally invasive transforaminal lumbar interbody fusion in the elderly: a systematic review and meta-analysis

Abstract: OBJECTIVE Minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) may be used to treat degenerative spinal pathologies while reducing risks associated with open procedures. As an increasing number of lumbar fusions are performed in the aging United States population, MIS-TLIF has been widely adopted into clinical practice in recent years. However, its complication rate and functional outcomes in elderly patients remain poorly characterized. The objective of this study was to assess complication ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This may be related to the long duration and high risk of injury associated with multi-segmental surgery. According to one investigation, MIS-TLIF has a higher rate of postoperative complications in multiple segments than in single segments ( 35 ). MIS-TLIF also has the disadvantage of requiring a significantly higher number of intraoperative radiations compared with the open TLIF group.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the long duration and high risk of injury associated with multi-segmental surgery. According to one investigation, MIS-TLIF has a higher rate of postoperative complications in multiple segments than in single segments ( 35 ). MIS-TLIF also has the disadvantage of requiring a significantly higher number of intraoperative radiations compared with the open TLIF group.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple systematic reviews and meta-analyses provide further evidence to support this observation [25][26][27][28]. O'Toole et al [24] conducted a study and discovered that surgical wound infections were significantly lower in MI-TLIF (0.6%) than in open TLIF procedures (4.0%).…”
Section: Infectionmentioning
confidence: 96%
“…Another study by Claus et al [22] directly contradicts the findings above by suggesting that morbid obesity (body mass index >40 kg/m 2 ) was not associated with either objective outcomes, postoperative complications, readmissions or adjacent segment disease. A pooled meta-analysis by Huang et al [24] of 12 studies suggested that patient age (>65 years) and multilevel fixation were independently linked to higher major and minor complication rates, however, with no effect on objective patient reported outcomes.…”
Section: Preoperative Considerations Affecting Complication Ratementioning
confidence: 99%